2018
DOI: 10.1016/j.bbi.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Negative and positive affect as predictors of inflammation: Timing matters

Abstract: Very little research has assessed how measures of negative and positive affect (NA and PA) derived from assessments at multiple time points per day (e.g., via ecological momentary assessment [EMA]), as opposed to questionnaires that rely on recall over a longer period, are related to levels of peripheral inflammation. We examined how different indicators of NA and PA predicted concentrations of C-reactive protein (CRP) and seven peripheral inflammatory cytokines (IL-1β, IL-6, TNF-α, IL-8, IL-4, IL-10, and IFN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 58 publications
6
59
2
Order By: Relevance
“…For example, momentary positive emotion was linked with lower levels of CRP and IL-6 among midlife women (Steptoe, O'Donnell, Badrick, Kumari, & Marmot, 2008). Further, in a diverse sample of mid-life adults, momentary negative affect was associated with higher levels of a composite of inflammatory cytokines that included IL-6 and TNF-a (Graham-Engeland et al, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…For example, momentary positive emotion was linked with lower levels of CRP and IL-6 among midlife women (Steptoe, O'Donnell, Badrick, Kumari, & Marmot, 2008). Further, in a diverse sample of mid-life adults, momentary negative affect was associated with higher levels of a composite of inflammatory cytokines that included IL-6 and TNF-a (Graham-Engeland et al, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…In the workplace, positive mood did predict positive emotional contagion between workers and clients [87]. Individuals with negative mood are more likely to report being less physically active [90], poor health [91], presented delays in wound healings [92], worsening prolonged or chronic illnesses [93] and to experience less success in the adherence of treatment for illnesses [94]. Delayed PA phases have also been consistently associated with symptoms of depression [95].…”
Section: Relevance and Implications Of Findingsmentioning
confidence: 99%
“…Most current research has tested for inflammation using acute inflammatory markers such as C-reactive protein (CRP) or IL-6, which are then used to predict current or recently experienced affect or depressive symptoms. In this vein, a recent study found empirical evidence that the relationship between inflammation and affect is a dynamic process and can vary daily ( Graham-Engeland et al., 2018 ). The Graham-Engeland et al.…”
Section: Introductionmentioning
confidence: 99%
“…We also sought to address methodological and statistical considerations raised from previous work (e.g. Graham-Engeland et al., 2018 ; Shrout et al., 2018 ; Rooijen et al., 2006 ), and finally, we discuss what implications these findings may have for future work in inflammation-related outcomes such as microbiome research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation